CENTRAL VERTIGO SYNDROME AS A CLINICAL MANIFESTATION IN ALCOHOL INTOXICATION - irfan pranowo (Faculty of Medicine Universitas Kristen Duta Wacana, 2018)
ABSTRACT Background : Vertigo syndrome is one of the clinical features in patients with alcohol intoxication. Cerebellar dysfunction (ie, ataxia, sluured speech, and nystagmus) generally occurs in a state of toxicity with greater alcohol concentration, a condition caused by involvement in the brainstem. Among the neurological complications of alcoholism, brainstem lesions are often present in Wernicke-Korsakoff syndrome, cerebellar degeneration, and central pontine myelinolysis.3 Objective: To Describe a central vertigo case in alcohol intoxication patient Case Description: A 21-year-old male, with a neck complaint that feels left and right pulled, since 1 day before admission. felt appeared 8 times. followed with dizzines, mild-moderate intensity, with symptoms of heartburn and nausea. Patients is an alcohol drinkers since 8 years ago, and active smokers who can spend a day a pack of cigarettes. On examination was found sufficient nutritional status, blood pressure 117/73 mmHg, pulse 80x / minute, respiration 22x / minute, temperature 36,8o C, and scale VVS 2. From physical examination obtained vertical and bidirectional horizontal nystagmus. The results of routine blood laboratory examination found blood leukocyte level 12.12 x103 / uL, others in normal limit Therapy: injection omeprazole 1 amp / 12 hours, flunarizin 5 mg / 12 hours, alprazolam 0.5 mg / 24 hours. After 3 days treatment, he was discharged with clinical improvement. Conclusions: An Alcohol intoxication patients in the presence of central vertigo syndrome in this case showed clinical improvement after treatment, then patients were advised to routine control.